Composition of the Essential Oil, Neutral Volatile Oil and Petroleum Ether Extract from Allium sativum of Different Regions in Korea and Antioxidant Activity - Chung, Ill-Min; Praveen, Nagella; Hyun Kim, Seung; Ahmad, Ateeque (Asian Journal of Chemistry, 2011)
The composition of the essential oil, neutral volatile oil and petroleum ether extract from the bulbs of Allium sativum of two different regions in Korea were analyzed and identified by gas chromatographic-mass spectrometry (GC-MS). The essential oil yields (mL/100 g dry weight) were for the Yeongcheon (I) 0.40 % and Uiseong regions (II) 0.30 %, respectively. Twenty and twenty eight compounds comprising 97.91 and 84.95 % of the total peak area were identified in essential oil of Yeongcheon and Uiseong regions, respectively. Twenty seven and twenty nine compounds comprising 87.45 and 99.42 % of the total peak area were identified in neutral volatile oil of Yeongcheon and Uiseong regions, respectively. Thirty one compounds each comprising 93.61 and 95.68 % of the total peak area were identified in petroleum ether extract of Yeongcheon and Uiseong regions, respectively. The major components of essential and neutral volatile oil were dimethyl trisulfide (DMTS), diallyl disulfide (DDS), trisulfide di-2- propenyl (TSDP), methyl 2-propenyl disulfide, 2-vinyl-[4H]-1,3-dithiin (2-VDT), 3-vinyl-[4H]- 1, 2-dithiin (3-VDT), 3-vinyl-1,2-dithiocyclohex-5-ene. The major components of petroleum ether extract were dimethyl trisulfide, phenylacetylene-2-d, DDS, 3-VDT, 2-VDT, TSDP, 1- propene 3,3'-thiobis. The identity of components of essential oil, neutral volatile oil and petroleum ether extract was confirmed on the basis of retention time, mass and supplemented library of NIST, USA. The neutral volatile oil and petroleum ether extract constituents are identified for the first time in garlic bulbs. The essential oil, neutral volatile oil and petroleum ether extract from the garlic bulbs were investigated for scavenging of the diphenylpicrylhydrazyl (DPPH) radical activity and the results demonstrate that the essential oil and the neutral volatile oil showed remarkable activity than the petroleum ether extract. Thus in general, garlic has potential as a natural antioxidant and thus inhibits undesired oxidation process.